Avaliação de técnicas cirúrgicas para cistostomia em ovinos com obstrução uretral induzida - Douglas Kiarelly Godoy de Araujo (2011)
Laparotomy (G1), laparoscopy (G2), and transcutaneous approach (G3) for implantation of a Foley catheter in ram lambs with induced urethral obstruction were compared to determine the best option for small ruminants with obstructive urolithiasis. The 18 animals used were randomly allocated into the three groups described above. From each individual, the penis was exposed and the urethral process obstructed with 3-0 polycot for 12 hours. The determined surgical procedure was performed for tube cystostomy. If the bladder was teared during surgery, the procedure would then change to laparotomy after cavity lavage and the data of this animal would be treated statistically as an additional group (G4). Surgical time was measured for each group. Heart rate, respiratory rate, rectal temperature, hematocrit, white and red blood cell count amd platelets were measured before the obstruction, immediately before surgery, and after ¹/2, 1, 2, 4, 8, and 15 days of surgery. A post-surgical complications scale was calculated for each animal in each time after the procedure. Additionally, serum concentrations of urea, creatinine, calcium, phosphorus, chloride, magnesium, potassium, and sodium were measured before and after surgery to test for significant changes caused by urine retention. A correlation matrix was calculated between these variables to test how the heart rate, respiratory rate, and rectal temperature correlate with the laboratory parameters. The transcutaneous approach was performed in less time than other techniques, but without statistical difference. Laparoscopy was less time-consuming when compared to laparotomy and laparotomy after a ruptured bladder. Overall the complication score fell over time, except for G3, which presented sensitive growth in the 8th post-operative day. The heart rate, respiratory rate, rectal temperature, and white blood cell count changed significantly (P<0.05) over time. Red blood cell count and hematocrit had a falling trend, but without any significant alterations. The blood platelet count was significantly different between groups G4 (higher) and G1 before surgery. Serum urea (37.0 to 55.8), creatinine (.6 to 1.2), and magnesium (2.1 to 2.4) increased (P<0.05) and phosphorus (7.3 to 5.6), calcium (10.1 to 9.5), and chloride (102.5 to 99.3) fell after 12 hours of urethral obstruction (values in mg/dl). These changes were all significant at P<0.05. Non-relevant changes were the concentation of serum potassium (6.2 to 4.4 mmol/l) and sodium (131.7 to 133.0 mg/dl). The most important correlations found regarding post-surgical complications were for heart rate (positive) and rectal temperature (negative), both after urethral obstruction. Surgeons should preferably choose laparoscopy for Foley catheter placement in sheep with urethral obstruction. A period of 12 hours of urethral obstruction produces leukocytosis, azotemia, hypocalcemia, hypophosphatemia, and hypochloremia, without significantly changing magnesium, potassium, and sodium concentrations. These changes lead to higher heart rate and to lower rectal temperature.